CDD Initiatives in Mainstreaming Gender in Northeast Brazil : An Exploratory Case Study - Amazonas, Fatima (World Bank, Washington, DC, 2017)
The present study focuses on gender while analyzing the effects of the Rural Poverty Reduction Project (RPRP) on the use of time and income generation as well as on cultural and social capital aspects. The study was based on a pilot project in Rio Grande do Norte designed to reinforce actions of the RPRP's focus on gender. The study should be viewed only as an exploratory evaluation that can be indicative of project effects, since the sample used was small and the time span between the subproject's implementation and the collection of impact data was short (only one year). However, other measures in the methodology guarantee a satisfactory minimum level of rigorousness in the evaluation, such as the comparison to a control group taken from a pipeline population of potential beneficiaries and a before-and-after approach to the analysis. The integration of gender concerns into World Bank poverty-reducing programs has been implemented by promoting inclusive development, ensuring that both women and men have a voice in the development of their community and benefit from new development opportunities. Part of this strategy is to advance women's economic empowerment by enhancing their ability to participate in land, labor, financial, and product markets. The current study was conducted simultaneously with the pilot project in order to document its results and, when possible, draw lessons that could be helpful in new operations. The study estimates, on a preliminary basis, how community investments that save women's time in household activities by themselves or combined with investments in production create the enabling environment for women's economic empowerment and, eventually, help reduce poverty.